Analisis Implementasi Prinsip 5C Untuk Meningkatkan Kualitas Kredit Guna Bhakti di BJB KCP Palima - Mei Yanti Br Surbakti; Enok Nurhayati; Fiesty Utami (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The aim of this research is to determine the quality of the implementation of 5C in Credit Guna Bhakti (KGB) and how to overcome problems that arise as a result of implementing the 5C principles at Bank BJB KCP Palima. This research method uses observation, interviews and literature study. The results of the research show that the quality of Guna Bhakti Credit at Bank BJB applies the 5C principles to prospective debtors, namely consisting of economic conditions, capacity, character, capital and collateral. 2023 will be considered smooth. Problems in implementing 5C occur in the principles of Character and Collateral. This character problem can be overcome by the bank being more careful in trusting the debtor, while regarding the Collateral principle, the bank must re-examine the prospective documents provided as collateral.